2015
DOI: 10.1016/j.renene.2015.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alumina nanoparticles, ethanol and isopropanol blend as additive with diesel–soybean biodiesel blend fuel: Combustion, engine performance and emissions

Abstract: a b s t r a c tExperimental investigation was carried out to study the combustion, engine performance and emission characteristics of a single cylinder, naturally aspirated, air cooled, constant speed compression ignition engine, fuelled with two modified fuel blends, B20 (Dieselesoybean biodiesel) and dieselesoybean biodieseleethanol blends, with alumina as a nanoadditive (D80SBD15E4S1 þ alumina), and the results are compared with those of neat diesel. The nanoadditive was mixed in the fuel blend along with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(117 citation statements)
references
References 26 publications
7
104
0
6
Order By: Relevance
“…Use of nano-additivesis a new technology that improves the ignition delay period, calorific value and emission characteristics of the diesel engine [15]. An inclusion of nanoparticles, especially nano metal oxides acts as a catalyst in the combustion process which helps in enhancing the combustion characteristics that improves the performance and emission characteristics of the engine [16]. Nanoparticles have high surface area to volume ratio that improves the contact between fuel and oxidizer, furthermore nanoparticles are high energy density additives that causes an increase in the calorific value of the fuel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of nano-additivesis a new technology that improves the ignition delay period, calorific value and emission characteristics of the diesel engine [15]. An inclusion of nanoparticles, especially nano metal oxides acts as a catalyst in the combustion process which helps in enhancing the combustion characteristics that improves the performance and emission characteristics of the engine [16]. Nanoparticles have high surface area to volume ratio that improves the contact between fuel and oxidizer, furthermore nanoparticles are high energy density additives that causes an increase in the calorific value of the fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Mina Mehregan et al numerically investigated on combustion characteristics of ethanol and n-decane liquid fuels blended with nano aluminium. It has been observed that the reduction in flame temperature, droplet evaporation rate and improved radiation by adding nano aluminium compared to pure ethanol and ndecane [16]. J. Sadhik Basha et al carried out an investigation on the effect of alumina nanoparticles blended with biodiesel water emulsion on the performance, combustion and emission characteristics of a diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…As observed from Table , the calorific value is increased with AON addition which acts as the influential parameter for the higher rate of heat release by nanofuels. The oxygen available in alumina leads to complete combustion because of the enhanced combustion rate, which is the main impact of adding nanoalumina to the fuel . Another reason is the improved ignition quality due to the increase in the cetane number of the nanofuel.…”
Section: Resultsmentioning
confidence: 99%
“…The highest power increase is related to B5 at 2500 rpm in which power increases by 15%. This is due to incomplete filling of the cylinder during the intake stroke at higher speeds although the valves are fully open [24][25][26][27]. There is not enough time for air intake and subsequently raising the cylinder pressure, which leads to the reduction of combustion pressure.…”
Section: Effect Of Speed Load and %Bd Variations On Engine Performancementioning
confidence: 99%